VD_FINDINFO HC / 2012 / 617 vom 2. Oktober 2012 - VD Tribunal cantonal (2012)
PROTECTION DE LA PERSONNALITÉ, LIBERTÉ DE LA PRESSE, MESURE PROVISIONNELLE | 28 CC, 52 CC, 37 LADB, 4 al. 2 LADB, 261 al. 1 CPC (CH), 59 al. 1 CPC (CH), 60 CPC (CH)